Pharmacological Characterization of Itch-Associated Response Induced by Repeated Application of Oxazolone in Mice - Yukihito Tsukumo; Daisuke Harada; Haruhiko Manabe (Elsevier, 2010)
We investigated pharmacological characteristics of the itch-associated response to chronic dermatitis induced by 4-ethoxymethylene-2-phenyl-2-oxazolin-5-one (oxazolone) repeated application in mice. Application of an oxazolone challenge to mice with oxazolone-induced chronic dermatitis evoked severe and transient scratching behavior for up to 1h. Thereafter, mild and continuous scratching behavior was observed for at least 8 h. Both severe and continuous scratching behaviors were suppressed by the opioid-receptor antagonist naltrexone, but not by the H1 histamine-receptor antagonist fexofenadine, 5-hydroxytryptamine-2 (5-HT2)-receptor antagonist methysergide, NK1-receptor antagonist LY303870, cyclooxygenase inhibitor indomethacin, or the platelet-activating factor-receptor antagonist YM264. The severe scratching behavior was suppressed by the 5-lipoxygenase inhibitor zileuton and leukotriene B4-receptor antagonist ONO-4057, but not by the cysteinyl leukotriene-receptor antagonist montelukast. The continuous scratching behavior was suppressed by pretreatment with the non-selective muscarinic acetylcholine-receptor antagonist atropine and M3 muscarinic acetylcholine-receptor antagonist darifenacin. These results suggest that leukotriene B4 receptor and M3 muscarinic acetylcholine receptor are involved in the itch-associated response induced by repeated application of oxazolone in mice. Keywords:: itch, scratching, oxazolone, allergy, dermatitis